Tracing Mycobacterium ulcerans along an alimentary chain in Côte d’Ivoire: A one health perspective - Hammoudi, Nassim (PLoS Negl Trop Dis, 2020)
BACKGROUND: Mycobacterium ulcerans is an environmental mycobacterium responsible for an opportunistic, noncontagious tropical infection named Buruli ulcer that necrotizes the skin and the subcutaneous tissues. M. ulcerans is thought to penetrate through breached skin after contact with contaminated wetland environments, yet the exact biotopes where M. ulcerans occurs remain elusive, hence obscuring the epidemiological chain of transmission of this opportunistic pathogen. METHODOLOGY/PRINCIPAL FINDINGS: Polymerase chain reaction investigations detected M. ulcerans in 39/46 (84.7%) rhizosphere specimens collected in 13 Buruli ulcer-endemic areas in Côte d’Ivoire and 3/20 (15%) specimens collected in a nonendemic area (P = 5.73.E(-7)); only 3/63 (4.7%) sediment specimens from sediment surrounding the rhizospheres were positive in endemic area (P = 6.51.E(-12)). High-throughput sequencing further detected three PCR-positive plants, Croton hirtus, Corton kongensis and Oriza sativa var. japonica (rice), in the rectal content of two M. ulcerans-positive wild Thryonomys swinderianus grasscutters that were hunted in Buruli ulcer-endemic areas, while no PCR-positive plants were detected in the rectal content of two negative control animals that were farmed in a nonendemic area. CONCLUSIONS/SIGNIFICANCE: Our data suggest an alimentary chain of transmission of M. ulcerans from plants to T. swinderianus grasscutters and people that utilize T. swinderianus as bush meat in Buruli ulcer-endemic areas in Côte d’Ivoire. Guidance to adopt protective measures and avoid any direct contact with potentially contaminated rhizospheres and with grasscutter intestinal content when preparing the animals for cooking should be established for at-risk populations.